Simultaneous analysis of α-amanitin, β-amanitin, and phalloidin in toxic mushrooms by liquid chromatography coupled to time-of-flight mass spectrometry - Ahmed, Walid Husein Ali; Gonmori, Kunio; Suzuki, Masako; Watanabe, Kanako; Suzuki, Osamu (Forensic toxicology, 2010)
An entire procedure for simultaneous analysis of α-amanitin, β-amanitin, and phalloidin in mushrooms by liquid chromatography (LC) electrospray ionization (ESI) time-of-flight (TOF) mass spectrometry (MS) has been optimized and established. We used a hydrophilic interaction column TSK-gel Amide-80 3 μm for LC separation, which enabled the simultaneous detection of the three toxins and internal standard microcystin RR. After homogenizing mushroom debris with methanol acidified with trifluoroacetic acid, the extract solution was subjected to solid-phase extraction with an Oasis HLB cartridge. The eluate was applied to the LC-ESI-TOF MS instrument. The calibration curves for the three toxins showed good linearity over the range of 100–1000 ng/g. The detection limits (signal-to-noise ratio = 3) for α-amanitin, β-amanitin, and phalloidin were about 30, 30, and 10 ng/g, respectively. The recovery rates of the three toxins at 100, 500, and 1000 ng/g were in the range of 53.1%–69.6%. The accuracy and precision (both intraday and interday) at 100, 500, and 1000 ng/g ranged from 87.9% to 117% and from 3.58% to 15.6%, respectively. Using the present method, the concentrations of the three toxins in the caps, stems, and roots of the toxic mushroom Amanita virosa were measured. The described method should be applicable to measurement of the Amanita toxins in human specimens, such as urine and blood of poisoned subjects.